2001
DOI: 10.1103/physrevb.64.085330
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit interaction of electrons on a curved surface

Abstract: Abstract. Spin-orbit (SO) interaction of electrons confined near the curved semiconductor surface is studied. The curvature of surface determines the new mechanism of SO interaction which complements the known mechanisms occurring in planar systems. The specific cases of nanosphere and nanotube are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 16 publications
0
82
0
Order By: Relevance
“…39 that the interface contribution to the Rashba spin-orbit term in the 2D Hamiltonian 41 is related to discontinuity of the band parameters at the semiconductor heterointerface and that this contribution is an additional one to those connected with the space charge and/or the external electric field. The importance of the effects described by the Rashba term for the 2D electrons confined near the curved surface 42,43 and cylindrical semiconductor quantum dots 44 has been emphasized recently. The Rashba spin-orbit term in our spherical dots is a direct consequence of the GBCs for the envelope function.…”
Section: Discussionmentioning
confidence: 99%
“…39 that the interface contribution to the Rashba spin-orbit term in the 2D Hamiltonian 41 is related to discontinuity of the band parameters at the semiconductor heterointerface and that this contribution is an additional one to those connected with the space charge and/or the external electric field. The importance of the effects described by the Rashba term for the 2D electrons confined near the curved surface 42,43 and cylindrical semiconductor quantum dots 44 has been emphasized recently. The Rashba spin-orbit term in our spherical dots is a direct consequence of the GBCs for the envelope function.…”
Section: Discussionmentioning
confidence: 99%
“…The curved geometry of nanotubes induces SO coupling on the order of 10 −1 meV among the single-particle levels of the electrons. 18 While the curvature-induced SO coupling was envisioned previously for semiconductors, 25,26 for nanotubes it is the dominant mechanism. It was Ando 27 and others 28,29 who developed the first theories of SO coupling in nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Band splitting was found considering surface curvature effects [9], as well as in the electron spin resonance spectra of achiral CNTs derived by low-energy theory [10]. In an earlier work, we showed that the inclusion of the full lattice symmetry is essential for deriving spin-orbit (SO) effects in CNTs [11].…”
mentioning
confidence: 99%
“…As an example for chiral tubes, the band structures calculated including the SOI for three particular tubes, (6,4), (9,3), and (8,4) belonging to each of the three families, are shown in Fig. 4 around the Fermi level.…”
mentioning
confidence: 99%